Multiliteracy Pedagogy in Literature Learning for Students' Critical Thinking Skills - Ayyu Subhi Farahiba (Advances In Education Journal, 2025)
This study aims to explore the application of multiliteracy pedagogy in literature learning as an effort to train students' critical thinking skills. This research uses a conceptual analysis method based on existing literature resources with a berrypicking technique. The data collection technique was carried out with a literature search of documents, phenomena, and problems of multiliteracy pedagogy in Indonesia. The findings of this study provide the concept of multiliteracy pedagogy-based literature learning to train students' thinking skills through stages, namely exploration, critical analysis of literature, work production, and collaborative reflection. Through these stages students are encouraged to think critically, creatively, and analytically. Literary works are used to introduce students to complex themes, characters, and messages, so that they can observe, evaluate, and make judgements based on evidence. This research reinforces the concept of multiliteracies pedagogy as an innovative approach to literature learning, which includes the mastery of multimodal literacy (textual, visual and auditory) and higher-order thinking skills and connects multiliteracies pedagogy with 21st century learning dimensions, such as critical thinking, collaboration and creativity.